PERBEDAAN ORAL HYGIENE DENGAN MENGGUNAKAN CHLORHEXIDINE 0,2% DAN NACL 0,9% UNTUK MENCEGAH TIMBULNYA VENTILATOR ASSOCIATED PNEUMONIA (VAP) DI INTENSIVE CARE UNIT (ICU) RSUP dr. SOERADJI TIRTONEGORO KLATEN - Nur Widayati; Sigid Shalihien; Feri Catur Yuliani (STIKES DUTAGAMA KLATEN, 2015)
Background: The incidence of pneumonia in sufferers being treated in the ICU is one form of nosocomial infections. VAP is one of the founders of factors of complications from Acute Respiratory Distress Syndrome (ARDS). VAP incidence figures can be reduced by having the care oral hygiene is good and correct. oral hygiene solution Clorhexidin 0.2% effective in preventing colonization of Staphylococcus Aureus. Research objectives: knowing the difference of Oral hygiene by using Chlorhexidine 0.2% 0.9% Nacl and to prevent the occurrence of Ventilator Associated Infection (VAP) in patients hospitalized in ICU Dr. Soeradji Tirtonegoro Klaten. Research methods: the research was included in a quasi experiment design or artificial treatment with non equivalent control group design. Engineering samples are non probability sampling with technical purposive sampling. Data analysis techniques using Paried test T test. Results of research: Characteristics of respondents ages 41-60-year-old as much as 9 (64,3%) respondents. Diagnosis of the disease the patient Post Craniotomy Operation by as much as 5 (35.7%) respondents. The male gender as much as 9 (64.3S%) of the respondents. The difference in Oral Hygiene use Clorhexidine obtained results VAP the value of p = 0.023 and because p < 0.05 0.05 then the Ha accepted and Ho is rejected. Conclusion: There is a significant difference between the oral hygiene of events VAP value mean different 1.428 oral hygiene means using Clorhexidine was able to lower the incidence of VAP figure 1.428 versus oral hygiene using Nacl 0.9%.